South African political economy insights : the story of the Walmart-Massmart merger - Gaylard, Alison; Draper, Peter ([London] : SAGE, 2016)
Two years after US retail giant Walmart had given notice of its intent to buy a majority shareholding in Massmart, the CEO of Massmart Holdings - Grant Pattison - reflected on how much had happened since then, and how much he had learnt through a merger process, which had become a protracted legal battle. The Competition Appeal Court had, however, just given its final ruling on the matter. Looking back, he wondered what he would have done differently, had he known that the approval process would not be plain sailing.
Originally Published in: Gaylard, A., & Draper, P. (2012). South African Political Economy Insights: The Story of the Walmart-Massmart Merger. WBS-2012-8. Johannesburg: The Case Centre, Wits Business School.
Description based on online resource; title from home page (viewed on April 26, 2016).
Keywords: elektronické knihy; electronic books; Wal-Mart (Firm); Massmart (Firm); Consolidation and merger of corporations -- Case studies